2021
DOI: 10.1093/toxsci/kfab047
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MEG3 Involved in NiO NPs-Induced Pulmonary Fibrosis via Regulating TGF-β1-Mediated PI3K/AKT Pathway

Abstract: Long noncoding RNA maternally expressed gene 3 (MEG3) involves in fibrotic diseases, but its role in nickel oxide nanoparticles (NiO NPs)-induced pulmonary fibrosis remains unclear. The present study aimed to explore the relationships among MEG3, transforming growth factor-β1 (TGF-β1) and phosphoinositide 3-kinase (PI3K)/AKT pathway in NiO NPs-induced pulmonary fibrosis. Wistar rats were intratracheally instilled with NiO NPs twice a week for 9 weeks, and human lung adenocarcinoma epithelial cells (A549 cells)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…Our former study proved that MEG3 decreased in A549 cells after treatment with NiO NPs 26 . To further explore the effect of MEG3 on the p38 MAPK pathway, we used 100 μg/ml NiO NPs to treat A549 cells, LV‐NC A549 cells and LV‐MEG3 A549 cells for 24 h. According to Figure 10, NiO NPs group did not differ from NiO NPs + LV‐NC group ( p > .05).…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…Our former study proved that MEG3 decreased in A549 cells after treatment with NiO NPs 26 . To further explore the effect of MEG3 on the p38 MAPK pathway, we used 100 μg/ml NiO NPs to treat A549 cells, LV‐NC A549 cells and LV‐MEG3 A549 cells for 24 h. According to Figure 10, NiO NPs group did not differ from NiO NPs + LV‐NC group ( p > .05).…”
Section: Resultsmentioning
confidence: 87%
“…Furthermore, our former study found that the expression of MEG3 was downregulated after NiO NPs exposure both in vivo and in vitro 26 . Additionally, lncRNA MEG3 regulated lung inflammation induced by cigarette smoke extract 54 .…”
Section: Discuissionmentioning
confidence: 86%
See 3 more Smart Citations